Decentralization and environmental governance in multicultural areas: lessons from two Colombian communities - Velasco, Marcela, author (Colorado State University. Libraries, 2012)
Most Latin American countries recognized the right to self-determination of ethnic groups and became precursors in community forest management. The paper takes the case of Colombia to evaluate how multicultural areas have adapted to these reforms. I evaluate the effect of local politics on ethnic organizations and environmental governance by comparing an indigenous community settling 1,300 hectares of forested land in Karmata Rúa (Antioquia) and a riverine Afro-Colombian community addressing the environmental effects of a hydroelectric company in the Anchicayá River (Valle). The paper argues that in multicultural areas, ethno-political autonomy may lead to environmental governance. Autonomy is affected by the scale and characteristics of ethnic territories and their natural resources, social movement dynamics, type of state presence and inter-government relations, and the reciprocal recognition and adaptation of consuetudinary and statutory norms within multiple layers of governance. I conclude that autonomy rights depend on local faculties to oversee government actions and synchronize customary and statutory rights. This is more likely to happen in the presence of strong social movements that support community empowerment and facilitate governance technology transfers compelling cooperation or acquiescence from government, and other powerful groups. I draw information from primary and secondary documents, participant observation and interviews with stakeholders.
Paper presented at the 2012 Annual Meeting of the American Political Science Association held in New Orleans, Louisiana on August 30 - September 2, 2012.
Keywords: conservation strategy; autonomy rights; grassroots movements; collaboration; environmental governance processes; Indigenous groups; Latin America